Komunikasi Pemasaran melalui Pemanfaatan Media Sosial dalam Promosi Guwang Village Festival - Anggreswari, Ni Putu Yunita; Parasari, Nyoman Sri Manik; Maheswari, A.A. Istri Agung (Jurnal Representamen, 2022)
The Covid-19 pandemic has paralyzed various sectors in Bali, especially the tourism sector. The recovery of various tourism destinations after the pandemic is a responsibility for tourism actors and all levels of society. One of the recovery steps taken is to carry out the Guwang Village Festival. The implementation of the Guwang Village Festival aims to revive several tourist destinations in Guwang village, as well as introduce various works of art from Guwang Village SMEs. This study uses a qualitative approach, with three data collection technique which include observation, documentation, and interview techniques. The results of this study are that promoting the Guwang Village Festival is carried out using the AIDDA communication model consisting of Awareness, Interest, Desire, Decision, and Action. The use of the AIDDA communication model was carried out through the use of Instagram social media so that the Guwang Village Festival managed to get 10.000 visits. Utilization od social media is done by presenting information, conducting social interactions, and providing entertainment facilities. Keywords: Marketing Communication, Social Media